STIGMA DAN PROSES SOSIALISASI WARIA SERTA DAMPAKNYA PADA PENINGKATAN RISIKO PENULARAN IMS DAN HIV/AIDS - Husni Abdul Gani; Dewi Rokhmah (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
Being a transvestites is assumed as deviate behaviour by our society. It is severed with negative stigmatization as bad image, dirty, criminal, and having deviate sexual orientation, cause this group of people have more risky toward psychological and sexual impact in transmision of STD and HIV/AIDS. Sosialization proces is needed by transvestitesgeting acceptance in social environment, because transvestites could not separate from social context. This study aims to analyze the stigmatization and sosialization process toward transvestites and its impact for the increasing of transmission risk from STD and HIV/AIDS.It was a qualitative study involved informants aged 25-54 with purposive sampling in Semarang city. Data was collected by indepht interview and they’re analyzed by thematic content analysis. The result of this study showed that stigmatization to transvestites was derived from public society and religius community. This rejection impacts at sosialization process in family, work place and society. Because our society assume transvestites identical with deviate behaviour from the norm, and having tranvestites as the family member means ignominy. Consequently they choose as a urbant people. It cause the increasing of transmission risk on STD and HIV/AIDS. There are no obstacle in sosialization process with other transvestites in cebongan. Cebongan is the place they can express themself without rejection from others. So they can be received as normal individual. Society is expected accepting them as a part of their live, with involved them include transvestites with HIV/AIDS in society activity.Key words : Transvestites, stigmatization, sosialization process, STD and HIV/AIDS